A case report of a fulminant Aeromonas hydrophila soft tissue infection in a patient with acute lymphoblastic leukemia harboring a rare translocation. (3rd July 2022) - Charakopoulos, Emmanouil; Diamantopoulos, Panagiotis T.; Zervakis, Konstantinos; Giannakopoulou, Nefeli; Psichogiou, Mina; Viniou, Nora-Athina
Abstract: Introduction: Aeromonads are gram-negative opportunistic bacteria, mainly found in aquatic environments. Hematologic patients are particularly at risk of Aeromonas soft tissue infections and septicemia, especially during chemotherapy-induced neutropenia. Case description: A 46-year-old man was diagnosed with acute lymphoblastic leukemia characterized by the rare t (12;17)(p13;q21)/ TAF15-ZNF384 aberration. On day 22 of chemotherapy, he developed febrile neutropenia followed by necrotizing fasciitis in his upper right extremity. Despite appropriate antibiotic therapy and prompt surgical intervention, he died within 36 h after the appearance of a fever. A multi-sensitive Aeromonas hydrophila was isolated from all cultural sites. Discussion and conclusions: In a previous paper we characterized the patient's aberration with cytogenetic and FISH analysis. Here, we provide details regarding the patient's rapidly progressing infection and underline the importance of maintaining high clinical suspicion of Aeromonas infections in acute leukemia. Given the unusually rapid progression of an infection caused by a rare non-resistant pathogen, and after considering data on the implication of metalloproteinase function in immune system regulation, a correlation between risk of severe infection and TAF15-ZNF384 aberrated acute lymphoblastic leukemia cannot be ruled out.